An Interactive Atlas: Taman Mini Indonesia Indah (TMII) Through International Eyes - Hally Hanafiah; Akari Lynn; Kaung Khant Kyaw; Thiri Maung Maung Zaw (Lentera Ilmu Madani, 2026)
This paper presents reflections and insights from one day trip visit to Taman Mini Indonesia Indah (TMII) undertaken by a group of international students. TMII, a cultural and educational park in Jakarta, provides a valuable journey through Indonesian’s rich cultural diversity and national philosophies. Through the exploration of TMII’s regional pavilions, museums and religious sites, the group gained a deeper understanding of Indonesian culture, Pancasila, citizenship values, religious pluralism and the importance of Bahasa Indonesia as a unifying language. This learning opportunity effectively integrated Pancasila studies, citizenship education, language practice and religious appreciation. It highlighted the role of TMII as an interactive resource that link cultural gaps and encourages the global awareness of Indonesia’s plural identity.